Relações hídricas e fotossíntese em espécies lenhosas de um cerrado stricto sensu em São Carlos, SP - Rojas, Manuel Humberto Cardoza (Universidade Federal de São Carlos, 2002)
Values of pre dawn, initial, and morning (between 10:00-11:30 h) leaf water potential (Ψaa, Ψi, and Ψ, respectively), and morning leaf gas exchange were obtained during wet and dry seasons in woody species of cerrado stricto sensu vegetation located at Southeast of Brazil, in São Carlos municipality (21°58'S-47°52'W, 850 m a.s.l.). At first eight species were studied measuring the leaf water potential during daily courses in dry and wet seasons. Two daily courses were carried out per season. In wet season the meteorological conditions were similar between the daily courses, when the maximum air temperature, vapor pressure deficit (VPD) and the total hours of direct solar radiation values were equivalent. Notwithstanding, the studied species showed different mean values of minimum (Ψmin) and integrated (IΨ) leaf water potential between the daily courses. In dry season the values of maximum temperature, VPD and the total hours of direct solar radiation values were much more different between the daily courses but there were not significant differences between Ψmin and IΨ mean values. The conditions at dry season (specially a moderate water stress at the rizosphere) could induce one distinct reaction since the early morning, promoting stomatal closing and avoiding great alterations in leaf water status. In chapter 1 were compared the average values of Ψmin among cerrado stricto sensu vegetation, Northern Australian savanna and Mediterranean Climate Vegetation. Because the rainfall is greater and more constant during the year in cerrado, and by reason of their woody species are able to cope the leaf water status during dry season, the values of Ψmin in cerrado were lower than Australian savanna (Mediterranean vegetation showed the lowest Ψmin). The results in chapter 2 confirmed the initial explanations in chapter 1 about the differences in Ψmin and IΨ in wet and dry seasons. In chapter 2 there are presented results of leaf gas exchange in 23 woody species: net photosynthesis (A), stomatal conductance (gs), transpiration (E), and sub stomatal CO2 concentration (Ci). All species studied (including those in chapter 1) showed reduced values of gs in dry season (78% on average basis) confirming that during the winter drought occurs sharp reduction of gs. This reduction was able to decrease the E values (-33%) due to the stomatal narrowing (lower values of gs under high values of VPD). It was probably responsible to increase the resistance for CO2 incoming to sub stomatal chamber, lowering the CO2 concentration available to photosynthesis. It could explain, at least in part, the lower mean A values under drought condition. Because A and E values decreased proportionally (around 32%), the water use efficiency mean values were kept equivalent during dry and wet seasons. In chapter 2 is proposed a diagram where are pointed out the principal causal events and the probable physiological responses for cerrado woody species under dry season.
Keywords: Fotossíntese - relações hídricas; Déficit de pressão de vapor; Potencial hídrico foliar; Cerrado; Trocas gasosas; CIENCIAS BIOLOGICAS::ECOLOGIA